Experience as a pedagogical artistic principle in the building of graduates in the performing arts (Papeles, 2017)
We present in a brief way the theoretical and practical conception and foundation of teacher training of performing arts program at the Antonio Nariño University (UAN). This pedagogical commitment is constructed in dialogue from approaches, among other theorists, such as Dewey’s scientism, to the background of the concept of vivencia (experience), collected by the teacher Delia Zapata Olivella (with the support of her brother the anthropologist Manuel Zapata Olivella), after years of touring the country and the world with her dance.
Keywords: experience; pedagogy; performing arts; principle in the building